Watch the hands: infants can learn to follow gaze by seeing adults manipulate objects. Issue 2 (4th January 2014) - Deák, Gedeon O.; Krasno, Anna M.; Triesch, Jochen; Lewis, Joshua; Sepeta, Leigh
Abstract Infants gradually learn to share attention, but it is unknown how they acquire skills such as gaze‐following. Deák and Triesch (2006) suggest that gaze‐following could be acquired if infants learn that adults' gaze direction is likely to be aligned with interesting sights. This hypothesis stipulates that adults tend to look at things that infants find interesting, and that infants could learn by noticing this tendency. We tested the plausibility of this hypothesis through video‐based micro‐behavioral analysis of naturalistic parent–infant play. The results revealed that 3‐ to 11‐month‐old infants strongly preferred watching caregivers handle objects. In addition, when caregivers looked away from their infant they tended to look at their own object‐handling. Finally, when infants looked toward the caregiver while she was looking at her own hands, the infant's next eye movement was often toward the caregiver's object‐handling. In this way infants receive adequate naturalistic input to learn associations between their parent's gaze direction and the locations of interesting sights.